Gifford Lecture 1: Genetic creativity: diversity and complexity in natural history - Rolston, Holmes, 1932-2025, speaker (Colorado State University. Libraries, 1997)
Central to the contemporary Darwinian view is emerging diversity and complexity. Genes are critical in this historic composition. In physics and chemistry, there is matter and energy, but in biology there is proactive information. Scientists divide over whether such evolution is contingent or directional. Elements of trial and error are incorporated in a searching generative process, analogous to genetic algorithms in computing.
Genetic creativity: diversity and complexity in natural history (Lecture 1 video)
Dr. Rolston delivers the first of his lectures in the Gifford lecture series. Recorded on November 10, 1997, at the University of Edinburgh, Scotland. Lecture series published as: Genes, Genesis and God: Values and their Origins in Natural and Human History. New York: Cambridge University Press, 1999.
Accessibility features: Captions and transcript.
Keywords: nature; ecosystems; self-organization; evolution; progress; biology; human genetics; genetics; natural history; creativity; complexity; Christianity; religion